Penyusunan Penilaian Kinerja Berbasis Kompetensi di Rumah Sakit XXX - Hernawa, Raditya; indiarto, Ferdinandus; Tresni, Lucia (HUMANITAS, 2014)
ABSTRACTThis study discusses the development of performance appraisal in XXX hospital. Currently, many employees are dissatisfied with the current performance appraisal tool because it is lack of objectivity. There is no feedback to employees and besides that performance appraisal is not relevant to the needs of hospital. To increase the objectivity of the performance appraisal tool, and maximize the performance appraisal objectiveness, the present study designed and developed competency base performance appraisal. This research is a qualitative research method by used interview data collection method. Competency-Based Performance Appraisal tested on cashier position. The results showed that the aspect of relevance, sensitivity, reliability and acceptability of new competencybased performance appraisal was better than the old performance appraisal. The implication will disccuss further.Keywords: Competency, Performance Appraisal